The first VLBI image of an infrared-faint radio source - Middelburg, E.; Norris, R.; Tingay, Steven; Mao, M.; Phillips, C.; Hotan, A. (EDP Sciences, 2008)
Context. We investigate the joint evolution of active galactic nuclei and star formation in the Universe. Aims. In the 1.4 GHz survey with the Australia Telescope Compact Array of the Chandra Deep Field South and the European Large Area ISO Survey – S1 we have identified a class of objects which are strong in the radio but have no detectable infrared and optical counterparts. This class has been called Infrared-Faint Radio Sources, or IFRS. 53 sources out of 2002 have been classified as IFRS. It is not known what these objects are. Methods. To address the many possible explanations as to what the nature of these objects is we have observed four sources with the Australian Long Baseline Array. Results. We have detected and imaged one of the four sources observed. Assuming that the source is at a high redshift, we find its properties in agreement with properties of Compact Steep Spectrum sources. However, due to the lack of optical and infrared data the constraints are not particularly strong.